Impacts of the North Atlantic Oscillation on Landslides - Zêzere, José (2019)
Western Iberia landslides are mostly triggered by rainfall, as, in fact, are most landslides worldwide. Results obtained using empirical relationships between rainfall amount and duration, and slope instability show that critical rainfall conditions for failure are not the same for different types of landslides.While rapid debris flows are usually triggered by very intense showers concentrated in just a few hours, shallow translational soil slips are most commonly triggered by intense precipitation falls within the 1–15 days long range. On the contrary, activity of the more deeply-seated landslides of rotational, translational and complex types is related to successive weeks of nearly constant rainfall, over periods of 30–90 days. Largescale patterns such as the El Niño and the North Atlantic Oscillation (NAO) change slowly and have been shown to have an impact in both the precipitation regime and the temporal occurrence of different landslide types in different areas of the world. In this work a particular attention is devoted to the impact of NAO on the landslide events that have occurred in the region located just north of Lisbon between 1956 and 2010. Results show that the large inter-annual variability of winter precipitation observed in Portugal is largely modulated by the NAO mode. The application of a 3-month moving average to both NAO index and precipitation time series allowed the identification of many months with landslide activity as being characterized by negative average values of the NAO index and high values of average precipitation (above 95 mm/month). Landslide activity in the study area is related to both intense, short duration precipitation events (1–15 days) and long-lasting rainfall episodes (1–3 months). The former events trigger shallow translational slides while the later episodes are usually associated with deeper and larger slope movements. The association between the NAO and landslide activity is shown to be more evident for the group of deep seated landslide events.